Problems on Commercialization of Genetically Modified Crops in Malaysia - Abdul Majid, Izaidin; Ismail, Kamariah; Tengku Azhar, T. N.; Yong, C. Y.; Aslan, A. S.; Wan Omar, Wan Zaidi (2012)
Modern biotechnology is a potential technology to be developed in Malaysia. Advancement in molecular genetics methods such as the recombinant DNA techniques in genetic engineering improves ways to make use of living organisms to benefit human. From the perspectives of agro biotechnology, the methods which enable the introduction of genetic material to be integrated into plant genome called Plant Genetic Modified Technology (PGMT). Since 1980s Malaysia enthusiastically worked on the development of Genetically Modified (GM) Crops. However, with certain barriers and hindrances, the successful development seems unattainable. This study was conducted to explore the six critical factors and issues which affect the successful commercialization of GM Crops in Malaysia using face to face and telephone interview which involved ten respondents from eight universities and research institutions in Malaysia. The data was analyzed using NVIVO computer software. The results from findings, recommendations and implications to practitioners presented.